2013
DOI: 10.1371/journal.ppat.1003129
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Antigen Expression and Epitope Presentation during Virus Infection

Abstract: Current knowledge about the dynamics of antigen presentation to T cells during viral infection is very poor despite being of fundamental importance to our understanding of anti-viral immunity. Here we use an advanced mass spectrometry method to simultaneously quantify the presentation of eight vaccinia virus peptide-MHC complexes (epitopes) on infected cells and the amounts of their source antigens at multiple times after infection. The results show a startling 1000-fold range in abundance as well as strikingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
132
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(148 citation statements)
references
References 86 publications
9
132
2
Order By: Relevance
“…Recently, data‐independent acquisition mass spectrometry has been applied for HLA‐I peptide discovery,41, 42 which, however, needs compatible instrumentation. Another possibility that was recently utilized for sensitive detection as well as quantification of HLA‐I peptides is targeted data acquisition 38, 43, 44, 45, 46, 47. Also in the present study, we used a targeted LC‐MS 3 approach, which is more sensitive for detection of HLA‐presented peptides than untargeted methods due to pre‐defined and pre‐programed analytes, resulting in longer acquisition times per analyte for increased sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, data‐independent acquisition mass spectrometry has been applied for HLA‐I peptide discovery,41, 42 which, however, needs compatible instrumentation. Another possibility that was recently utilized for sensitive detection as well as quantification of HLA‐I peptides is targeted data acquisition 38, 43, 44, 45, 46, 47. Also in the present study, we used a targeted LC‐MS 3 approach, which is more sensitive for detection of HLA‐presented peptides than untargeted methods due to pre‐defined and pre‐programed analytes, resulting in longer acquisition times per analyte for increased sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Such MS-based targeted platforms require a priori knowledge of the molecular targets. These techniques are routinely used within the proteomics community but were only recently applied for the sensitive detection and the robust quantification of MHC class I peptides (27,37,57,87,88). S/MRM is considered the gold standard quantification method for predefined sets of target peptides (84).…”
Section: Identification and Quantification Of Mhc-associated Peptidesmentioning
confidence: 99%
“…In this regard, previous studies showed that the sensitivity gain resulting from optimizing the collision energy for each transition was about twofold compared with the signals obtained from more generic collision energies computed according to the mass of the targeted precursor (92, 94, 96 -98). This optimization process could therefore be particularly beneficial for the detection of low-abundance MHC-bound peptides (27,88).…”
Section: Identification and Quantification Of Mhc-associated Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…have reviewed the three main data acquisition concepts in MS that have been applied in immunopeptidomics,2 commonly used in other proteomics MS workflows. These include: 1) data‐dependent analysis (DDA) which is the widely used strategy for so‐called “discovery experiments” where the researcher is interested in profiling the repertoire of pMHC from a given sample5, 6; 2) selected reaction monitoring (SRM), also referred to as multiple reaction monitoring (MRM), targeted analyses whereby ion signatures from both the peptide precursor and its fragmentation product ions are monitored, and the area under the curve or peak height can be used for quantification purposes; this method ensures a higher degree of selectivity than a DDA experiment, but at the expense of the experimental depth and throughput7; and 3) data independent analysis (DIA) strategies, where all peptides within a defined mass‐to‐charge ( m/z ) window are subjected to fragmentation and recording of their combined MS/MS spectra; the precursor isolation window sequentially marches up the full m/z range and this analysis is repeated again and again during chromatographic elution 8. This less mature technique promises excellent performance for both discovery and quantitative analyses, especially with regard to reproducibility and more accurate label‐free quantification 9…”
Section: Introductionmentioning
confidence: 99%